1 Characterization of Mature Beef Bull Seminal Fluid and Blood Serum Metabolome During a 65-Day Breeding Season. (22nd October 2022) - Williams, Jordan D; Field, Catherine E; Dubowsky, Jason; Banwarth, Megan; Cochrane, Tyree; Fanter, Rob; La Frano, Michael; McFarlane, Zachary D
Abstract: The American beef bulls have been neglected in terms of animal science research. Metabolomics is a respected for of science that will aid in developing hypothesis for future research in beef bulls. The objective of this study was to identify metabolites within a 65-day breeding season that were affect by breeding season duration and workload. Over a two-year period, 8 purebred Angus bulls owned and housed by the Cal Poly beef unit were surveyed using serum (collected via the coccygeal vein) and seminal fluid (collected via electroejaculation) at the beginning and end of a 65-day post-AI breeding season. Samples underwent HPLC-MS to observe metabolites within the fluids. Data were stratified for sample day and workload and compared using t-test for day and ANOVA for workload. Within serum, 8 metabolites of interest were observed. Effects included differences between workload groups in the abundance of guanosine (P = 0.01) a metabolite associated with purine metabolism. Within seminal fluid, 13 metabolites of interest were observed including Inosine, a metabolite also involved in purine metabolism and fluctuating based on workload (P = 0.05). Purine metabolism will be of interest to future research of beef bulls.